Discovery of Novel GLUT4 Inhibitors from Kawista (Limonia Acidissima L.) Bioactive Compounds Through in Silico Approaches - M. Artabah Muchlisin; Engrid Juni Astuti; Aura Lintang Ayu Cahyani; Felia Rahma Cahya Andita; Nur Islami Vikri Abdillah; Aghnia Fuadatul Inayah; Taufik Muhammad Fakih (JRST (Jurnal Riset Sains dan Teknologi), 2026)
GLUT4 (Glucose Transporter Type 4) is a key regulator of glucose homeostasis in muscle and adipose tissues. Although inhibition of GLUT4 may exacerbate hyperglycemia in diabetes, it represents a potential therapeutic strategy in cancer by limiting glucose uptake in cells reliant on aerobic glycolysis (the Warburg effect). Natural secondary metabolites are promising candidates for modulating GLUT4 activity. This study aimed to identify potential GLUT4 inhibitors from bioactive compounds of Limonia acidissima (kawista) using in silico approaches. Secondary metabolites of kawista were screened for ADMET properties and oral bioavailability. Molecular docking was performed against the cryo-EM structure of GLUT4 (PDB ID: 7WSM), followed by 200 ns molecular dynamics simulations for the top-ranked ligands. Structural stability was evaluated using RMSD, RMSF, radius of gyration (Rg), and solvent-accessible surface area (SASA). Binding free energies were calculated using the MM-PBSA method. Docking analysis showed that the native ligand cytochalasin B exhibited strong binding affinity (−9.13 kcal/mol, Ki 202.26 nM). Among 43 kawista metabolites, stigmasterol (−8.6 kcal/mol, Ki 494.04 nM) and lupeol (−7.91 kcal/mol, Ki 1.58 μM) demonstrated the most favorable binding affinities. Molecular dynamics simulations revealed stable protein–ligand complexes, with RMSD values ranging from 2.0 to 3.5 Å. RMSF analysis indicated stable key binding residues (Gln298, Gln299, Asn304, Gly400, Trp428, and Asn427), except for Trp404, which showed higher fluctuation in the lupeol complex. Rg and SASA values remained relatively constant, indicating compact and stable complexes. MM-PBSA analysis confirmed that stigmasterol exhibited the most favorable binding free energy, closely comparable to cytochalasin B. These findings suggest that stigmasterol and lupeol from Limonia acidissima are promising GLUT4 inhibitors, with stigmasterol demonstrating the most stable interaction and favorable binding profile. This study highlights the potential of kawista-derived metabolites as lead compounds for further development of GLUT4-targeted anticancer agents.